1963
DOI: 10.1007/bf02631548
|View full text |Cite
|
Sign up to set email alerts
|

A review on petroselinic acid and its derivatives

Abstract: This publication contains a comprehensive review of literature on petroselinic acid and its derivatives. All known sources of petroselinic acid including its synthetic derivation have been explored and described. The different plant species, whose seeds offer an oil reported to contain petroselinic acid, have been listed and the amounts of oil and their prevalent fatty acid components given. Its method of isolation from the naturally occurring triglycerides and identification have been discussed. The descripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
24
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 62 publications
5
24
1
Order By: Relevance
“…Petroselinic acid is the characteristic FA for seed oils of the plant order Umbelliflorae, where it occurs in high amounts. Levels of up to 85% have been reported in only three plant families (Umbelliferae, Araliaceae, and Garryaceae) (1,2). This acid has not been previously reported as a main component of seed oils from other than these three plant families, and this work extends the list of natural sources of petroselinic acid by the plant family Geraniaceae.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Petroselinic acid is the characteristic FA for seed oils of the plant order Umbelliflorae, where it occurs in high amounts. Levels of up to 85% have been reported in only three plant families (Umbelliferae, Araliaceae, and Garryaceae) (1,2). This acid has not been previously reported as a main component of seed oils from other than these three plant families, and this work extends the list of natural sources of petroselinic acid by the plant family Geraniaceae.…”
Section: Discussionsupporting
confidence: 54%
“…This extends the list of natural sources of these two unusual FA (2,8) by inclusion of the Geraniaceae plant family. As a part of our screening program of lesser-known seed oils, the seed oil of G. sanguineum was analyzed for its FA composition.…”
mentioning
confidence: 65%
“…Another study demonstrated that biodiesel fuels high in monounsaturated FAs yields superior fuel properties relative to those enriched in saturated or polyunsaturated FAs (Moser and Vaughn, 2012). Monounsaturated FAs may comprise 86% of FA profile of FSO (Placek, 1963).…”
Section: Introductionmentioning
confidence: 97%
“…The principal fatty acid (FA) in fennel seed oil (FSO) comprising 60-85% of the content is petroselenic acid (PA; C18:1 6c; 6Z-octadecenoic acid) (Charvet et al, 1991;Placek, 1963). PA is of particular interest because its oxidation yields lauric and adipic acids (Corma et al, 2007;Placek, 1963).…”
Section: Introductionmentioning
confidence: 99%
“…Petroselinic acid (C18:1 6) is the main fatty acid (up to 80%) in the fatty oil (Kleiman and Spencer, 1982). Coriander oil is of interest because of its potential application in oleochemistry (Placek, 1963). Petroselinic acid, an isomer of oleic acid, opens up another approach to the manufacture of medium chain fatty acids (MCFAs), since it can be split into lauric (C12:0) and adipic (C6) acids by oxidative cleavage.…”
Section: Introductionmentioning
confidence: 99%